The larva of Perilestes attenuatus Selys, 1886 (Odonata: Perilestidae) from Amazonas, Brazil - Neiss, Ulisses Gaspar; Hamada, Neusa (Zootaxa, 2010)
The larva of Perilestes attenuatus Selys, 1886 is described and illustrated based on exuviae of reared larvae and lastinstar larvae collected in Manaus, Amazonas state, Brazil. The larva of P. attenuatus can be distinguished from that of P. fragilis, the only other species of which the larva has been described, by the presence of a pair of tubercles on the ligula and by the arrangement of the spines and hooks on the abdominal segments.